A Proposed Framework for the Relationship between Emotional Intelligence and Employee’s Performance: Mediating Role of Job Demand - Mokhtar, Noorzalyla; Krishnan, Ramesh (Information Management and Business Review, 2023)
In the realm of employee performance, emotional intelligence (EI) plays a pivotal role. Research has consistently shown that EI is positively correlated with employee performance. It acts as a critical predictor, influencing how well employees perform in their roles. Emotional intelligence encompasses one’s ability to perceive, express, understand, and manage emotions. When employees possess high EI, they are better equipped to navigate the challenges and dynamics of the workplace. As there are scarcity of research that explains the mechanism describing the EI-Employee’s Performance relationship, this study proposed the potential role of job demands as an important mediator in this relationship. Job demands include factors like workload, stress, and time pressures. Employees with high EI tend to handle these demands more effectively, leading to reduced stress and burnout consequently increasing job performance. In summary, emotional intelligence serves as a reliable predictor of employee performance and is crucial for maintaining a motivated and high-performing workforce, ultimately benefiting the organization as a whole.